Insulin Independence in Newly Diagnosed Type 1 Diabetes Patient following Fenofibrate Treatment - Karsten Buschard; Laurits J. Holm; Ulla Feldt-Rasmussen (Case Reports in Medicine)
A 19-year-old girl was diagnosed with type 1 diabetes and showing polydipsia and polyuria. She was double autoantibody-positive and had a diabetes-prone tissue type. She was immediately started on insulin. Fenofibrate treatment (160 mg daily) was initiated seven days after diagnosis. The need for insulin quickly declined, and she took her last dose of insulin 19 days after the first dose of fenofibrate, having regained endogenous control of blood glucose concentrations. She has now been insulin independent for one year and 9 months. Unstimulated C-peptide has increased by 51% (317 to 479 pmol/l), and IA-2 autoantibody level has decreased by 65% (49 to 17 × 103 arbitrary units). Fenofibrate is a widely used drug for reducing triglyceride and cholesterol levels. Fenofibrate reverses and prevents autoimmune diabetes in nonobese diabetic (NOD) mice by increasing the amount of the sphingolipid sulfatide in islets. Sphingolipid metabolism is otherwise abnormal in the islets at diagnosis of type 1 diabetes. In conclusion, we describe a 19-year-old patient with classical newly diagnosed type 1 diabetes, which following fenofibrate treatment has been without insulin for 21 months.